Women Incumbents’ Political Marketing Communication in Matrilineal Society at Pesisir Selatan Regional People’s Representative Council - Handayani, Fitri (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Women and political marketing communication is an interesting topic to study in the middle of patriarchal political society. In a matrilineal society like West Sumatera, the application is only for private affairs like maternal lineage and inheritance of heirloom. Meanwhile the public affair is dominated by patriarchal politics, resulting in low presentation by women in politics. This study uses qualitative descriptive case study to find the success rate of political marketing communication by women incumbents in matrilineal society in one of West Sumatra’s regency, Pesisir Selatan. This study dissects Integrated Marketing Communication (IMC) theory and Brand Loyalty to look into strategies in winning votes. Socialization, training, coaching, Focus Group Discussion and active participation in community organization hold very important roles. Other strategies like radios, billboard, banner and online media are additional political marketing communication. Analysis shows that the success rate of women marketing communication strategy depends on the proof of performance and the ability to mingle in the society of Minangkabau.